2016
DOI: 10.1093/aje/kww082
|View full text |Cite
|
Sign up to set email alerts
|

The Intracranial Distribution of Gliomas in Relation to Exposure From Mobile Phones: Analyses From the INTERPHONE Study

Abstract: When investigating the association between brain tumors and use of mobile telephones, accurate data on tumor position are essential, due to the highly localized absorption of energy in the human brain from the radiofrequency fields emitted. We used a point process model to investigate this association using information that included tumor localization data from the INTERPHONE Study (Australia, Canada, Denmark, Finland, France, Germany, Israel, Italy, Japan, New Zealand, Norway, Sweden, and the United Kingdom).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The major results were published after a delay of 6 years in 2010 [2]. In a new publication the intracranial distribution of glioma in relation to RF radiation from mobile phones was analyzed [44]. Tumour localization for 792 regular mobile phone users was analyzed in relation to distance from preferred ear for mobile phone use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major results were published after a delay of 6 years in 2010 [2]. In a new publication the intracranial distribution of glioma in relation to RF radiation from mobile phones was analyzed [44]. Tumour localization for 792 regular mobile phone users was analyzed in relation to distance from preferred ear for mobile phone use.…”
Section: Resultsmentioning
confidence: 99%
“…The tumour volume was larger in glioma cases using wireless phones compared with nonusers. It should also be noted that α was higher in larger glioma tumours with shortest distance from preferred ear to tumour center which might be an effect of tumour promotion [44]. Several studies have shown an increasing incidence of glioma, especially glioblastoma multiforme in the temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…In the INTERPHONE and some other studies, the risk of glioma tended to be higher in individuals who reported the usual MP use on the same side of the head as their tumors [40,41]. However, the ipsilateral effect found in low exposure groups suggested that patients might have over-reported the use of MPs on the tumor side (recall bias) [41,43]. Bias is known to occur in the epidemiologic research: the dose-dependent selection and selfselection, observation, participation, recall bias, etc.…”
Section: Epidemiological Researchmentioning
confidence: 92%
“…In the large multicenter INTERPHONE study, no increase in the risk of glioma or meningioma was observed in MP users. There were suggestions of an elevated glioma risk at the highest exposure levels, but potential bias prevented a causal interpretation [41,43]. A re-analysis of Canadian data from the INTERPHONE study showed significant results for glioma; comparing the quartile with the highest MP use to those who were not regular users [odds ratio: 2.2 (95% limits: 1.3, 4.1)].…”
Section: Epidemiological Researchmentioning
confidence: 99%
“…The RF-EMR emitted from Wi-Fi transmitter involves whole body exposure (Wu et al 2010;Banaceur et al 2013) while mobile phone involves localized RF-EMR exposure (Ozorak et al 2013;Grell et al 2016;Jamaludin et al 2017). RF-EMR is classified as non-ionizing radiation and theoretically is unable to induce ionization of cellular atoms and molecules.…”
Section: Introductionmentioning
confidence: 99%